Revision Rates and Causes in Total Hip Replacement: A Systematic Review - Andriessanto Ceelvin Lengkong (Journal of World Science, 2024)
Total hip replacement is a common surgery to treat severe hip joint pain and dysfunction. Although total hip replacement is generally safe and effective, complications, including revision, are risks. This study aimed to systematically review the literature to analyze revision rates and causes of total hip replacement. This research uses a systematic literature review method following PRISMA guidelines. The data collection technique in this research uses literature study techniques. Literature searches were conducted in electronic databases such as PubMed, Scopus, and Google Scholar. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and conclusion. The results showed that factors such as infection, dislocation, limb length discrepancy, and other complications play an important role in determining the revision rate and success of replacement. Precautions include using a povidone-iodine mouthwash before treatment to reduce the risk of infection and implementing better blood management protocols to optimize total hip replacement results. This study implies an in-depth understanding of the risk factors associated with revision total hip replacement, which is essential in managing patients undergoing this procedure. By paying closer attention to these factors, medical practitioners can increase the success of total hip replacement and reduce the number of revisions required, thereby improving patients' quality of life.